2018
DOI: 10.1007/s11105-018-1077-z
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MPK6 as Mediator of Ethylene/Jasmonic Acid Signaling in Serendipita indica-Colonized Arabidopsis Roots

Abstract: Serendipita indica is an axenically cultivable fungus, which colonizes a broad range of plant species including the model plant Arabidopsis thaliana. Root colonization by this endophyte leads to enhanced plant fitness and performance and promotes resistance against different biotic and abiotic stresses. The involvement of MPK6 in this mutualistic interaction had been previously shown with an mpk6 A. thaliana mutant, which failed to respond to S. indica colonization. Here, we demonstrate that mpk6 roots are sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…But, this biotrophic phase is followed by a cell death-associated colonization phase, revealed to occur through induction of endoplasmic reticulum (ER) stress and suppression of unfolded protein response, resulting in ER swelling and activation of a γVPE/caspase 1–like-mediated cell death program, preceded by vacuolar collapse (Schäfer and Kogel, 2009; Qiang et al, 2012). Colonization with P. indica was also shown to reduce the availability of free sugars and amino acids to the root tip, to change host hormone homeostasis and to be dependent on efficient suppression of plant immune responses (Schäfer et al, 2009; Daneshkhah et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…But, this biotrophic phase is followed by a cell death-associated colonization phase, revealed to occur through induction of endoplasmic reticulum (ER) stress and suppression of unfolded protein response, resulting in ER swelling and activation of a γVPE/caspase 1–like-mediated cell death program, preceded by vacuolar collapse (Schäfer and Kogel, 2009; Qiang et al, 2012). Colonization with P. indica was also shown to reduce the availability of free sugars and amino acids to the root tip, to change host hormone homeostasis and to be dependent on efficient suppression of plant immune responses (Schäfer et al, 2009; Daneshkhah et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Symbiosis between plants and microbes is a very common ecological relationship. Host plants obtain diverse benefits from the symbiosis involving the improvement of nutrition availability (Bertolazi et al, 2019), yields (Xia et al, 2016) and tolerance against abiotic as well as biotic stresses (Daneshkhah, Grundler & Wieczorek, 2018;Song et al, 2015). In this study, the occurrence rates of F. oxysporum and F. fujikuroi on leaf surface of I. cairica reached up to 100% regardless of habitat.…”
Section: Fujikuroimentioning
confidence: 64%
“…Similar to what we observed in S. vesicarium -infected onions, in a precedent study [ 44 ] we had shown that P. indica was responsible for an enhanced expression of Solanum lycopersicum chitinases, in the late stages of A. solani infection. Daneshkhah et al [ 110 ] also confirmed that P. indica -mediated upregulation of PR chitinases could hardly be noticed in A. thaliana roots in the early stages of infection, during the biotrophic colonisation phase, and was expressed later in time, at the cell death-associated stage. As suggested by Van Wees et al [ 67 ] chitinase regulation is primarily driven by ET/JA signalling pathway.…”
Section: Discussionmentioning
confidence: 98%
“…Basic and acidic chitinases belong to the glycosyl hydrolase family and are involved in plant disease resistance mechanisms [ 108 ]. Due to their role in fungal cell wall degradation, they are included among the pathogenesis-related (PR) proteins and are significantly induced in response to necrotrophic fungal infections [ 109 , 110 ]. Similar to what we observed in S. vesicarium -infected onions, in a precedent study [ 44 ] we had shown that P. indica was responsible for an enhanced expression of Solanum lycopersicum chitinases, in the late stages of A. solani infection.…”
Section: Discussionmentioning
confidence: 99%